Cluster analysis of microscopic spatio-temporal patterns of tourists' movement behaviors in mountainous scenic areas using open GPS-trajectory data. (December 2022) - Liu, Wenbao; Wang, Bingxue; Yang, Yang; Mou, Naixia; Zheng, Yunhao; Zhang, Lingxian; Yang, Tengfei
Abstract: Understanding spatio-temporal patterns of tourist movement behaviors is vital for Destination Management Departments (DMDs) on destination planning, marketing, and resource management. This study uses open GPS-trajectory data to analyze the microscopic spatio-temporal patterns of tourists' movement behaviors in Mount Huashan in China. Two major measures, Markov chains and cluster analysis, are used to cluster tourists into groups to show their spatio-temporal movement behaviors within the study site. The Markov chain analysis unveiled three kinds of spatial patterns on microscopic tourists' movement: "proximity transfer", "span transfer" and "hub transfer", while the cluster analysis further demonstrated three kinds of microscopic spatio-temporal patterns: "day-climbing", "night-climbing", and "full-day sightseeing". These results provide vital implications for tourism management of the mountainous scenic areas in general and in Mount Huashan in particular. Graphical abstract: Image 1